2017
DOI: 10.5797/jnet.cr.2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Endovascular Hemostatic Technique Using N-butyl Cyanoacrylate for Retroperitoneal Hematoma Caused by Inferior Epigastric Artery Injury after Undergoing Catheter Ablation for Atrial Fibrillation: A Case Report

Abstract: Objective: N-butyl cyanoacrylate (NBCA) is used as a liquid embolic agent in various hemorrhagic situations with a high technical success rate and low recurrent bleeding rate, especially in patients with coagulopathy.Case Presentation: An adult patient was admitted to the intensive care unit with coagulopathy and hemorrhagic shock.Past medical history of the patient included dual-antiplatelet therapy and warfarinization for several cardiac diseases.Retroperitoneal hematoma caused by femoral artery (FA) branch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 6) Recently, embolization with NBCA for vascular injury related to femoral artery puncture has been increasingly reported. 7) NBCA is easy to adjust the concentration, which can be sufficiently embolized to the distal part of injured vessel and expected to have a high hemostatic effect. However, regurgitation or migration into a normal blood vessel may occur; therefore, technical skills are required.…”
Section: Discussionmentioning
confidence: 99%
“… 6) Recently, embolization with NBCA for vascular injury related to femoral artery puncture has been increasingly reported. 7) NBCA is easy to adjust the concentration, which can be sufficiently embolized to the distal part of injured vessel and expected to have a high hemostatic effect. However, regurgitation or migration into a normal blood vessel may occur; therefore, technical skills are required.…”
Section: Discussionmentioning
confidence: 99%
“…reported that in iatrogenic IEA injury, 11% of cases were occurred by percutaneous puncture at the femoral site. 4 Anti-coagulant therapy is one of the risk factors for bleeding. The IEA injuries have been treated through surgery and transcatheter embolization.…”
Section: Discussionmentioning
confidence: 99%